2016
DOI: 10.1371/journal.pone.0165441
|View full text |Cite
|
Sign up to set email alerts
|

Oral Ondansetron versus Domperidone for Acute Gastroenteritis in Pediatric Emergency Departments: Multicenter Double Blind Randomized Controlled Trial

Abstract: The use of antiemetics for vomiting in acute gastroenteritis in children is still a matter of debate. We conducted a double-blind randomized trial to evaluate whether a single oral dose of ondansetron vs domperidone or placebo improves outcomes in children with gastroenteritis. After failure of initial oral rehydration administration, children aged 1–6 years admitted for gastroenteritis to the pediatric emergency departments of 15 hospitals in Italy were randomized to receive one oral dose of ondansetron (0.15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 33 publications
1
35
0
4
Order By: Relevance
“…In einer doppelblinden randomisierten kontrollierten Studie aus Italien wurde die 1-malige orale Gabe von Ondansetron, Domperidon oder Placebo bei Kindern mit einem aufgrund von Erbrechen gescheiterten ersten Rehydrationsversuch verglichen [146]. Eine nachfolgende intravenöse Flüssigkeitstherapie war bei 11,8 % der Patienten in der Ondansetron-und 25,2 % der Domperidonbzw.…”
Section: Ii28 Empfehlungunclassified
“…In einer doppelblinden randomisierten kontrollierten Studie aus Italien wurde die 1-malige orale Gabe von Ondansetron, Domperidon oder Placebo bei Kindern mit einem aufgrund von Erbrechen gescheiterten ersten Rehydrationsversuch verglichen [146]. Eine nachfolgende intravenöse Flüssigkeitstherapie war bei 11,8 % der Patienten in der Ondansetron-und 25,2 % der Domperidonbzw.…”
Section: Ii28 Empfehlungunclassified
“…This is a selective serotonin receptor blocker that inhibits initiation of the vomiting reflex in the periphery. Recently, it has been demonstrated that ondansetron reduces the risk of intravenous rehydration by over 50%, both with placebo and domperidone . However, a clearance on safety in children is needed before a final recommendation is made, because of a warning regarding possible cardiac effects (such as prolongation of the QT interval) .…”
Section: Vomitingmentioning
confidence: 99%
“…A systematic evaluation of all Cochrane reviews evaluating commonly used interventions in children with vomiting due to acute gastroenteritis by Freedman et al 29 showed significant reduction in hospital admission and intravenous rehydration rates with oral ondansetron use.This is a selective serotonin receptor blocker that inhibits initiation of the vomiting reflex in the periphery. Recently, it has been demonstrated that ondansetron reduces the risk of intravenous rehydration by over 50%, both with placebo and domperidone 30. However, a clearance on safety in children is needed before a final recommendation is made, because of a warning regarding possible cardiac effects (such as prolongation of the QT interval) 31.…”
mentioning
confidence: 99%
“…Como alternativa à metoclopramida, a administração de fármacos com segurança bem estabelecida, como o ondansetron e a domperidona (apesar de antidopaminérgico, atravessa a barreira hemato-encefálica em reduzidas quantidades, ao contrário da metoclopramida), é aconselhada. 1,5…”
Section: Comentáriounclassified